Exploring recruits' motivations to enter policing in Small Island Developing States: The case of the Trinidad and Tobago Police Service. (December 2021) - Wallace, Wendell C.
Internationally, there is a substantial amount of research on motivations to enter the police profession; however, scant research attention has been paid to the motivations of individuals in Small Island Developing States (SIDS) such as Trinidad and Tobago who choose policing as a career path. As a result, this research was designed to analyze motivations for entering the police profession by gathering data from recruits who had recently entered police academy training in Trinidad and Tobago. The research utilized a quantitative approach with self-administered questionnaires as the data-gathering instrument. Using data collected from 160 police recruits at the Trinidad and Tobago Police Service (TTPS) police academy who were two months into their induction training, this study attempts to answer four questions related to their motivations for entering policing. Statistical analyses of the data included comparisons between groups in the sample (males/females) to determine the existence of competing motivations. The results indicate that job security was the main motivation for entry into the TTPS and that the motivations of male recruits were more altruistic when compared with those of female recruits, which were generally self-serving. Other results and implications for policy are discussed.